2017
DOI: 10.1051/parasite/2017030
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology ofSarcocystis neuronaandNeospora hughesiinfections in domestic donkeys (Equus asinus) in Durango, Mexico

Abstract: There is currently no information regarding Sarcocystis neurona and Neospora hughesi infections in donkeys in Mexico. Here, we determined the presence of antibodies against S. neurona and N. hughesi in donkeys in the northern Mexican state of Durango. Serum samples of 239 domestic donkeys (Equus asinus) were assayed for S. neurona and N. hughesi antibodies using home-made enzyme-linked immunoassays; six (2.5%) of the 239 donkeys tested seropositive for S. neurona. The seroprevalence of S. neurona infection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Studies show the appreciable links of H. pylori seropositivity, which has a minimal rate of recurrence of consuming various meats [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show the appreciable links of H. pylori seropositivity, which has a minimal rate of recurrence of consuming various meats [11].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Garcia-Bocanegra et al (20) reported that the seroprevalence of T. gondii was higher in animals that were kept outdoors than in those kept indoors. Moreover, Alvarado-Esquivel et al (4) observed that horses generally received better care than donkeys in terms of the quality of fodder and drinking water. Our results are compatible with those of previous studies from different countries (21,35), which show higher seroprevalence in donkeys.…”
Section: Componentmentioning
confidence: 99%